THE INTERRELATIONSHIP BETWEEN HEALTH PRESERVATION AND PEDAGOGICAL TECHNOLOGIES IN THE TRAINING OF SPECIALISTS AT HIGHER EDUCATIONAL INSTITUTIONS (Physical Culture and Sport: Scientific Perspective, 2025)
The article outlines certain aspects of the use of health-preserving technologies in the training of specialists in educational institutions. The introduction of health-preserving technologies in the educational process is connected with the use of medical and hygienic, physical and wellness, social-adaptive, ecological health-preserving technologies, and technologies ensuring safety. Using health-preserving technologies in the educational process allows for a comprehensive assessment of living conditions, preserving physical and mental potential in young people, forming a higher level of health, developing a healthy way of life, monitoring indicators of individual development, forecasting possible health changes, and implementing corrective and rehabilitation measures in appropriate psychological-pedagogical ways to improve quality of life and create favorable educational environments. However, such technologies cannot be detached from the general pedagogical system, and must be used systematically, purposefully, and rationally in conjunction with others.In the field of health preservation, education, and training of pedagogical specialists, the effective combination of health-preserving technologies is key to ensuring that students develop health-preserving competencies, improve their health, and engage in more responsible social and public health activities.The goal of all health-preserving educational technologies used at Yuriy Fedkovych Chernivtsi National University is to develop students’ necessary knowledge, skills, and abilities for a healthy lifestyle and to teach them how to apply this knowledge in everyday life. The implementation of health-preserving technologies in the educational process of higher education institutions allows students to adapt more successfully to the educational, social, and societal environment, unlock their creative potential, and enables educators to effectively prevent antisocial behavior among students.The main elements of health-preserving educational technologies are related to the following activities:• integrating health-preserving educational technologies into all forms of the educational process;• creating optimal conditions for their effective implementation in the learning process;• coordinating and managing the implementation of these technologies in education.
Keywords: health; competency; health-preserving competencies; pedagogical technologies; professional training